Problems of Justice in Legal Protection Efforts against Banks as Separatist Creditors related to Execution of Collateral Tied with Mortgage Rights on Bankrupt Debtor's Assets - Soetansah, Ilham; Emirzon, Joni; Yahanan, Annalisa (Faculty of Law, Universitas Pattimura, 2022)
Introduction: The rights of banks as separatist creditors in the UU-KPKPU cannot be implemented. Banks also often get a share that is not under the amount of debtor debt, causing injustice.Purposes of the Research: This study aims to analyze and explain the forms of justice problems in legal protection efforts against banks as separatist creditors related to the execution of collateral tied with mortgage rights on the assets of bankrupt debtors and their solutions.Methods of the Research: This research uses normative legal research. Research materials were used, namely secondary data and primary data as a support. This research material was collected by document study and interviews. The material that has been collected is then processed and analyzed using a qualitative approach, which is then drawn to conclusions using the deductive method.Results of the Research: There are two forms of the problem of justice in the legal protection of banks as separatist creditors related to the execution of collateral tied with mortgage rights on the assets of the bankrupt debtor. First, the neglect of bank rights as separatist creditors by UU-KPKPU can be seen in the provisions of Article 56 paragraph (1) and 59 paragraph (1) which contradicts Article 55 paragraph (1). Second, banks as separatist creditors often get a share that is not under the amount of debt of the bankrupt debtor. The author suggests that the UU-KPKPU be changed based on distributive justice which requires proportional distribution.